CLINICOHAEMATOLOGICAL SPECTRUM OF PANCYTOPENIA IN A TERTIARY CARE HOSPITAL - Khan, Taj Ali; Khan, Irfan Ali; Mahmood, Khalid (Journal of Postgraduate Medical Institute, 2013)
Objective: To determine the frequency, clinical presentation and underlying causes of pancytopenia inpatients presenting to a tertiary care hospital in Peshawar. Methodology: This cross-sectional, observational study was conducted at Department of Pathology,Lady Reading Hospital Peshawar from January to December 2011. Patients of all ages havingpancytopenia on blood film examination (TLC < 4000/ul, Hb < 10 gm/dl and Platelets < 150000/ul) wereincluded in the study. Already diagnosed patients of Aplastic Anemia, Acute Leukemia receiving treatmentand those not willing for bone marrow examination were excluded from the study. History, GeneralPhysical and systemic examination were recorded at presentation. The peripheral blood counts wereperformed with sysmex – automated hematology analyzer. Bone marrow aspiration and trephine biopsywere performed according to the standard protocol and examined microscopically to find the underlyingcause of pancytopenia. Other relevant investigations were also done. Results: During the study period, we received 600 patients for bone marrow examination from variousunits. Out of these, 160 (26.7 %) patients had pancytopenia. Common clinical presentations were Pallor(95%, n=150), followed by generalized weakness (75%, n=120), fever (52%, n=83), bleeding manifestation(37.5%, n=60), gastrointestinal symptoms (32.5%, n=52) and splenomegaly (23.5%, n=38). The commoncauses of pancytopenia were aplastic anemia (37.5%, n=60) followed by magaloblastic anemia (13.75 %,n=22), Acute Leukemia (13.75%, n=22) and hypersplenism (10%, n=16). Conclusion: Pancytopenia is a common occurrence. Aplastic Anemia and Magaloblastic Anemia are thecommonest causes of Pancytopenia followed by Acute Leukemia. Common clinical presentations werePallor, fever, weakness, bleeding manifestation and Splenomegaly.